STATUS, PROBLEMS AND PROSPECTS OF ACTIVITIES OF UKRAINIAN ENTERPRISES IN TODAY'S REALITIES - Тернова, Алла; Власенко, Ірина (SWorldJournal, 2024)
The article shows that the drop in production and the growth of unemployment is a key risk for the functioning of the Ukrainian economy. This is due to a reduction in production, a decrease in tax revenues and the country's GDP, and an increase in budget